2016
DOI: 10.26669/2448-409170
|View full text |Cite
|
Sign up to set email alerts
|

Compostos fenólicos extraídos de fontes naturais aplicados como conservadores em massas de pizza

Abstract: A melhoria nas práticas de higiene e produção de alimentos é importante para a segurança alimentar, além da necessidade de aplicação de conservantes de tipos e níveis corretos. A pizza é um dos alimentos que sofre intensa manipulação durante o processamento o que contribui para sua contaminação, perda de qualidade e um intervalo restrito de vida útil. Em vista disto, o objetivo do trabalho foi aplicar em pizzas compostos fenólicos extraídos do farelo de arroz fermentado pelo fungo Rhizopus oryzae e da microalg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, Spirulina has well-known culture conditions and has been used in food formulations or extraction of biocomposites. Studies have shown different biological actions can be identified on components of this microalga and its antifungal and antibacterial properties have being exploited [5,34,97,98].…”
Section: Microalgae As Potential Source Of Preservativesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Spirulina has well-known culture conditions and has been used in food formulations or extraction of biocomposites. Studies have shown different biological actions can be identified on components of this microalga and its antifungal and antibacterial properties have being exploited [5,34,97,98].…”
Section: Microalgae As Potential Source Of Preservativesmentioning
confidence: 99%
“…Christ et al [97] applied phenolic compounds from Spirulina LEB-18 as preservatives in the formulation of pizza dough's. It was verified promising effect of microalgae extracts instead of chemical preservative propionate to inhibitory mold and yeast counts until 10 days after the formulation of the pizza dough.…”
Section: Microalgae As Potential Source Of Preservativesmentioning
confidence: 99%